Stillbirth After Adolescent and Young Adult Cancer: A Population-Based Study. (27th August 2022) - Murphy, Caitlin C; Betts, Andrea C; Allicock, Marlyn A; Shay, L Aubree; Preston, Sharice M; Cohn, Barbara A; Lupo, Philip J; Pruitt, Sandi L
Abstract: Background: Gonadotoxic effects of cancer treatment may increase risk of adverse birth outcomes in adolescent and young adult (AYA, aged 15-39 years) women diagnosed with cancer. We estimated risk of stillbirth (fetal death of gestational age ≥20 weeks or weighing ≥350 grams) in a population-based sample of AYA women. Methods: AYA women diagnosed with cancer between January 1, 1995, and December 31, 2015, were identified using the Texas Cancer Registry and linked to live birth and fetal death certificates through December 31, 2016. Among AYA women, cumulative incidence of stillbirth was estimated by gestational age, and Poisson regression models identified factors associated with stillbirth. Standardized fetal mortality ratios (SMR) compared the observed fetal mortality rate in AYA women with the expected fetal mortality rate in the general population. Results: A total of 11 628 live births and 68 stillbirths occurred to 8402 AYA women after diagnosis. Cumulative incidence of stillbirth in AYA women was 0.70% (95% confidence interval [CI] = 0.51% to 0.96%) at 40 weeks of gestation. Risk of stillbirth was higher among Hispanic (risk ratio [RR] = 2.64, 95% CI = 1.29 to 5.41) and non-Hispanic Black (RR = 4.13, 95% CI = 1.68 to 10.16) women compared with non-Hispanic White women; there was no association with receipt of chemotherapy or time since diagnosis. Age- and race and ethnicity–adjusted fetal mortality rate in AYA women was similar to the general population (SMR = 0.99, 95% CI = 0.77 to 1.26). Conclusions: AYA women may be counseled that overall risk of stillbirth is low, and for most, cancer does not appear to confer additional risk.